Effect of sedation on visual sensations in patients undergoing cataract surgery under topical anaesthesia: a prospective randomized masked trial. (13th September 2011) - Venkatakrishnan, Jaichandran V.; Kumar, Chandra M.; Ratra, Vineet; Viswanathan, Jagadeesh; Jeyaraman, Vijay A.; Ragavendera, Thennarasu
Abstract: Purpose: The main aim of the study was to determine whether intravenous sedation with midazolam reduces the ability of patients to see during cataract surgery performed under topical anaesthesia. We also sought to determine the effects of sedation on patient's level of disturbance to the microscope light and visualization of surgical instruments and on the overall of experience of the patients during surgery. Methods: A total of 78 patients, aged 40–75 years, were randomly divided into two groups: Group S, (sedation) who received intravenous midazolam 0.015 mg/kg, and Group NS, (no sedation) who did not receive midazolam. Patients with history of anxiety, those with history of intraocular surgery and those with severe chronic obstructive pulmonary disease were excluded. Topical anaesthesia was achieved by the application of 2% xylocaine gel over the conjunctiva. A blinded observer interviewed all the patients 30 min after the surgery using a standard questionnaire. Results: Significant number of patients (25.6%) in Group NS was disturbed a lot because of the microscope light compared to Group S (5.1%), p = 0.021. Also, statistically significant number of patients in Group S (48.7%) compared to Group NS (20.5%) was not sure about the images perceived during surgery and were unable to recollect them after the surgery, p = 0.008, and 12.8% of the patients in Group NS reported the visual experience as frightening compared to 2.6% of patients in Group S, p = 0.239. Conclusion: Our study confirms that intravenous midazolam reduces both the ability to see and recall intraoperative visual images in patients undergoing cataract surgery under topical anaesthesia.